A wear-resistant coating with combined mechanical and antifouling properties for potential underwater cleaning applications - Chen, Xiping; Du, Leika; Chen, Jiawang; Xu, Huanzhi; Zhang, Qinghua; Hu, Jiankun (Frontiers in Chemistry, 2025)
IntroductionSilicone-based low-surface-energy antifouling coatings are environmentally friendly, but their widespread application is hindered by the inherent challenge of achieving a balance between mechanical durability and antifouling efficacy.MethodsThis study developed a novel multifunctional anchoring material, N,N’-bis(12-hydroxystearoyl)-1,3-phenylenediamine (A), via a condensation reaction. Silicone antifouling coatings were then synergistically modified with A, molybdenum disulfide (MoS2), and polytetrafluoroethylene (PTFE), followed by room-temperature crosslinking to form a composite coating.ResultsThe incorporation of 1% A significantly enhanced the coating’s performance: surface roughness was reduced by 33% (from 1.12 μm to 0.75 μm), the water contact angle increased from 118.2° to 122.7°, and tensile strength was improved by 85% (from 1.08 MPa to 2.00 MPa). The elastic modulus increased by 130%, while underwater friction decreased by 64% (from 2.41 ± 0.09 N to 0.87 ± 0.04 N). The coating demonstrated exceptional durability, with an average surface roughness (Sa) remaining below 2.65 μm after 2000 abrasion cycles. Furthermore, it exhibited outstanding self-cleaning efficiency (>97.1 ± 0.87%) and antibacterial rates (>94.5 ± 1.78%). Marine field tests confirmed effective antifouling performance for over 90 days during peak fouling season.DiscussionThe synergistic effect of A, MoS2, and PTFE successfully overcame the key limitations of traditional low-surface-energy coatings—poor mechanical strength and weak wear resistance. This work provides a breakthrough in designing high-performance, durable antifouling coatings with strong potential for practical applications, particularly in underwater cleaning robotics.